Plug in battery electric car : design of high voltage system and its related mechanical structures - Lee, Jia Yao (2015)
Internal combustion engines (ICE) have dominated the automotive industry for decades, while the reach of its close competitor, the electrical motor had been limited to trains and recreation vehicle. There are two main reasons for this difference, the cost of production and the range of battery. As compare to ICE, electrical motor requires a battery to enable its flexibility of movement. However, the slow advancement of battery technology and high cost of production prevented the electrical motor from being a competitor of the ICE in the automotive industry. In recent years, growing interest in Electrical vehicle (EV) had been observed. This was motivated by environment concerns, rising oil prices and the recent advancement in battery technology. This project was initiated by Nanyang Technology University (NTU) to research and develop a plug in Battery Electric Vehicle (BEV), which is a key step for Singapore to gain an edge as the world races to develop the future of automobile. BEV is deem highly viable in Singapore, as travelling distance is short due to geographic limitation and limited natural resources such as oil. The electrical energy required by the EV could be filled using renewable sources therefore reducing reliance on oil import.